2018
DOI: 10.1093/jn/nxx067
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Intake and Type of Away-from- Home Foods Consumed Are Associated with Diet Quality in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL)

Abstract: Background: Away-from-home foods (AFHFs) influence diet quality, a modifiable obesity risk factor, with limited generalizable evidence in Hispanic/Latino adults. Objective: We investigated associations between AFHF intake with diet quality and overweight or obesity among US Hispanic/Latino adults. Methods: Cross-sectional baseline (2008-2011) analyses included adults (n = 16,045) aged 18-74 y in the national Hispanic Community Health Study/Study of Latinos. Participants self-reported AFHF consumption frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
(58 reference statements)
1
19
0
Order By: Relevance
“…This study tries to address a bit deeper research question regarding the non-linearity. If marginal effects of FAFH on health outcome appear to not be linear, it may comprise positive to negative (or negative to positive) marginal effects, which was not manifested in the prior studies ( [29][30][31][32]). In this sense, the subsequent research question that deserves to be investigated is the optimal level of frequency of having FAFH that results in the best health outcome such as minimizing obesity.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This study tries to address a bit deeper research question regarding the non-linearity. If marginal effects of FAFH on health outcome appear to not be linear, it may comprise positive to negative (or negative to positive) marginal effects, which was not manifested in the prior studies ( [29][30][31][32]). In this sense, the subsequent research question that deserves to be investigated is the optimal level of frequency of having FAFH that results in the best health outcome such as minimizing obesity.…”
Section: Introductionmentioning
confidence: 82%
“…In other words, multi-level hypothetical treatments of the frequency of FAFH are investigated in this study. Prior studies that have shown non-linear relationship between frequency of having FAFH and health outcomes estimate the effects by applying a regression model for consumer groups divided by FAFH frequency (Fulkerson et al [30], Seguin et al [31] and McClain [32]). Therefore, self-selection bias remains an issue.…”
Section: Introductionmentioning
confidence: 99%
“…A 2018 report from the USDA, Economic Research Service found employed individuals reported higher weekly frequencies of food away from home compared to those unemployed [35]. Intake of meals prepared outside the home and convenience foods or 'ready-meals' is prevalent among Hispanic/Latino adults and has been associated with poorer diet quality and health outcomes [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Kids expected parents to provide guidance on how much to eat and some reported they need permission before getting second helpings at meals. Depending on parents to determine portion size can be troublesome as children mature and increasingly eat away from their families [ 47 ] because kids will not be equipped to make portion size decisions independently. Furthermore, if children are accustomed to determining how much to eat by the amount parents serve them, it is possible children will overeat when served large restaurant portions.…”
Section: Discussionmentioning
confidence: 99%